Deflating the LLSVPs: Bundles of Mantle Thermochemical Plumes Rather Than Thick Stagnant "Piles". Issue 10 (25th September 2020) - Davaille, Anne; Romanowicz, Barbara
Abstract: Based on SEMUCB‐WM1 tomographic model, validated by other recent models, and fluid mechanics constraints, we show that the large low shear velocity provinces (LLSVPs) present at the base of the Earth's mantle beneath the Pacific and Africa do not extend as compact, uniform structures very high above the core‐mantle boundary. In contrast, they contain a number of well‐separated, low‐velocity conduits that extend vertically throughout most of the lower mantle. The conceptual model of compact piles, continuously covering the areal extent of the LLSVPs, is therefore not correct. Instead, each LLSVP is composed of a bundle of thermochemical upwellings probably enriched in denser than average material. It is only when the tomographic model is filtered to long wavelengths that the two bundles of plumes appear as uniform provinces. Furthermore, the overall shape of the LLSVPs is probably controlled by the distribution of subducted slabs, and due to their thermochemical nature, the position of both LLSVPs and individual upwelling dynamics should be time dependent. There is also evidence for smaller plumes originating near the CMB in the faster than average regions of the voting map of Lekic et al. (2012, https://doi.org/10.1016/j.epsl.2012.09.014 ) as well as other, barely resolved, weaker plumes within the LLSVPs. These finer‐scale features are starting to be resolved tomographically owing to improvements in full waveform modeling of body waves, including diffracted S waves (Sdiff) and waves multiply reflected on the core‐mantle boundary (ScS) and their codas. Key Points: We use seismic tomography and fluid mechanics constraints to decipher the morphology of LLSVPs in the Earth's mantle The two LLSVPs do not extend as compact, continuous, and uniform piles above the core‐mantle boundary Each LLSVP corresponds to a bundle of several thermochemical plumes